Settlement of the costs of hot water used in multi-family residential buildings - Szaflik, Władysław; Stachel, Aleksander (Instal, 2024)
The article concerns the issue of settling the costs of hot water heating in multi-family residential buildings. In the beginning, the balance of heat necessary to provide the tenants with hot water at the right temperature was presented and discussed. Then, the methods of settling hot water costs in multi-family buildings were characterized. The impact of the volume of water consumption by individual premises on its unit price was analysed, with the currently used settlement methods. A method has been proposed that, in the opinion of the authors, allows for taking into account the actual amount of heat lost in the hot water system, and thus a fairer distribution of the cost of the amount of heat consumed for hot water needs among the tenants. For the newly occupied building, the results of calculations of heat cost allocation using the currently used method and the method proposed by the authors are presented. The differences between them are shown.
Keywords: hot water installations; energy demand for hot water; hot water price